Knowledge and skills for the use of interactive games with elderly (Research, Society and Development, 2020)
Objectives: to present knowledge of the gerontological care team on the potential of games and interpret the skills for their effectiveness through permanent education. Method: qualitative research, action-research type, in a long-term institution for the elderly in the metropolitan region of Rio de Janeiro, whose data collection instrument was an interview using a semi-structured script, with eighteen employees, under Bardin's analysis and dialogue with theoretical references from Maurice Tardif, Philippe Perrenoud and the policy of permanent health education. Results: three categories of analysis revealing knowledge about games and continuing education. Conclusions: the game offers innovations in the health field for comprehensive care for the elderly, with activities related to them, involving the multidisciplinary team, who ignores their potential, attributing only value to the elderly's cognitive development, or as a hobby, due to the absence of dialogues and the action-reflection-action movement, provided for in permanent health education, using the knowledge listed by Tardif, in order to develop the skills described by Perrenoud for effective care.